Combined Effects of % Er Coating and Ec: Pvp Ratio on Release Profile of Topiramate Extended Release Pellets - Patel, Vrunda (Asian Journal of Pharmaceutical Research and Development, 2020)
The main purpose of this study was to investigate the influence of %ER coating and EC: PVP ratio on the release profile of topiramate extended release pellets. This formulation comprises of an extended releasecomponent (ethyl cellulose) which retards the release of drug coated on the core pellets. The extent of extended release coat and concentration of extended release component is optimized to achieve predetermined dissolution profile. Formulating modified release drug delivery system for highly soluble drug is difficult.Presentresearchcomprisesofethylcelluloseactsasratecontrollinghydrophobicbarrier while povidone k-30 acts as pore former component which helps in release of drug. Reservoir technology by using wurster coating process was used to develop extended release pellets where, subsequent coating is applied on corepellets. In drug layering stage, drug solution prepared was dispersion solution. Therefore viscosity played animportantroleindruglayering. 4% barrier coating using Opadry clear was done to smoothen the drug layered pellets for the ease of subsequent coating process. Extended release coat applied on the barrier layer coated pellets, determines the release of the drug from the formulation. Thus, in present research ratio of EC: PVP K-30 and % ER coating were optimized to 75:15 and 13% respectively to obtain desired drug releaseprofile.